PANIC BUYING PHENOMENON AMONG ACADEMICS AT X UNIVERSITY IN SURABAYA - Rachma Rizqina Mardhotillah; Denis Fidita Karya; Azmil Chusnaini; Berto Mulia Wibawa (Jurnal Bisnis dan Keuangan, 2021)
In the weeks at the start of the pandemic, some news in Indonesia was colored related to the panic buying phenomenon by Indonesians in the midst of the Covid-19 pandemic. Of course, the Indonesian people were quite worried about the pandemic at that time. Starting from the scarcity of masks, hand soap and hand sanitizers at the beginning of the soaring positive cases of Covid-19 to the scarcity of staple goods consumed by everyday people such as sugar and rice, this phenomenon forced the government to impose restrictions on the purchase of staples. Currently, several regulations have been implemented regarding the purchase of basic commodities by the government to minimize hoarding activities of staple goods. This study aims to see the effect of the Covid-19 pandemic on the emergence of panic buying behavior among the academics of a university in Surabaya. The analytical method used in this research is descriptive analysis with a total sample of 60 respondents consisting of lecturers, students, and educational staff. The research was conducted from June to July 2020. After conducting a survey, it was found that many academics at X University Surabaya were not affected by the panic buying phenomenon.